The top 100 cited articles in menstrual health among adolescent girls: a citation analysis - G. Alekhya; Dinesh Prasad Sahu; Priyamadhaba Behera (BMC, 2023)
Abstract Background Menstrual health is an important public health concern where it is still considered a taboo, and adolescent girls often lack knowledge about menstrual health, face limited access to sanitation facilities, and struggle with the affordability of sanitary materials. Every year numerous articles are published; however, only a few of them would be influential in the evolution of a particular field. The number of citations received by an article serves as a quality factor for the impact of the article in a particular field. Citation analysis analyses the relationship between citations received by articles. From the literature search, no citation analysis was conducted on menstrual health. Hence the objective of the study was to identify the articles which received hundred or more citations and also to identify the leading countries, journals, study designs, and departments conducting research on menstrual health. Methods Citation analysis was done with search terms pertaining to adolescent and menstrual health using Google Scholar as a database in Publish or Perish software. The articles retrieved were exported to Microsoft Excel. Articles that received a hundred or more citations were screened for the type of article, department, and country where the study was conducted. A descriptive analysis of the hundred or more cited articles was done in Microsoft Excel. Results A total of 982 articles pertaining to menstrual health among adolescent girls were retrieved. There were hundred articles with hundred and more citations pertaining to the menstrual health of adolescent girls. Cross-sectional study design, Obstetrics and Gynaecology department, India and USA countries, and PLOS ONE journal had the most citations in research on menstrual health among adolescent girls. The top ten articles were on menorrhagia, menstrual hygiene practices, Water, Sanitation and hygiene (WASH), stigma on menstruation, and education on menstrual health. Conclusion The hundred cited articles on menstrual health among adolescent girls were mainly from high-income countries and were of more observational in nature than interventional. Thus, highlighting the need to strengthen experimental studies on the menstrual health of adolescent girls in Lower-middle-income countries.